2013
DOI: 10.1364/oe.21.004319
|View full text |Cite
|
Sign up to set email alerts
|

Blue-phase liquid crystal cored optical fiber array with photonic bandgaps and nonlinear transmission properties

Abstract: Blue-phase liquid crystal (BPLC) is introduced into the pores of capillary arrays to fabricate fiber arrays. Owing to the photonic-crystals like properties of BPLC, these fiber arrays exhibit temperature dependent photonic bandgaps in the visible spectrum. With the cores maintained in isotropic as well as the Blue phases, the fiber arrays allow high quality image transmission when inserted in the focal plane of a 1x telescope. Nonlinear transmission and optical limiting action on a cw white-light continuum las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 35 publications
1
33
0
Order By: Relevance
“…Recent studies have shown that another mesophase, namely, Blue-Phase Liquid Crystals (BPLC) present promising alternatives to NLC for electro-and nonlinear optics [32][33][34][35][36][37][38][39][40][41][42][43][44]. In this unique class of optical materials formed by mixing a chiral compound and nematics, the molecules self-assemble (without cell-surface alignment) into tightly wound defect-spirals that form 3-D body-centered cubic or simple cubic lattices with sub-wavelength lattice constants, cf.…”
Section: Intense Laser Induced Lattice Distortion In Bplc With Nanosementioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that another mesophase, namely, Blue-Phase Liquid Crystals (BPLC) present promising alternatives to NLC for electro-and nonlinear optics [32][33][34][35][36][37][38][39][40][41][42][43][44]. In this unique class of optical materials formed by mixing a chiral compound and nematics, the molecules self-assemble (without cell-surface alignment) into tightly wound defect-spirals that form 3-D body-centered cubic or simple cubic lattices with sub-wavelength lattice constants, cf.…”
Section: Intense Laser Induced Lattice Distortion In Bplc With Nanosementioning
confidence: 99%
“…Following the general discussion in previous sections, Maxwell Stress by the optical electric field of intense laser pulses will cause flows in transparent BPLC as well. Out studies [39,43] shown that in general, focused pulsed laser of intensity over several MW/cm 2 is required to generate observable effects. In the case of a Gaussian laser beam with a radial intensity distribution of the form…”
Section: Intense Laser Induced Lattice Distortion In Bplc With Nanosementioning
confidence: 99%
“…There have also been recent studies of another phase of chiral nematic liquid crystals, namely, Blue-Phase Liquid Crystals (BPLC) and their polymer-stabilized forms (PSBPLC) that presented promising polarization-and alignment-free alternatives [5,[92][93][94][95][96][97][98][99] for nonlinear optics as well as electro-optics. In this unique class of optical materials formed by mixing chiral and achiral nematics (with or without polymer stabilization), the molecules self-assemble into tightly wound defect-spirals that form 3-D cubic or BCC lattices with sub-wavelength lattice constants.…”
Section: Multiple Time Scales Nonlinearities Of Nematic Liquid Crystamentioning
confidence: 99%
“…In addition, owing to the subdued director axis fluctuations of the tightly wound cholesteric spirals, scattering loss and relaxation times of BPLC's are greatly reduced. This allows high transmission through much longer path lengths [94] and the generation of large phase shift with much lower threshold power requirement and faster response times than typical nematics. Since BPLC constituents are organic molecules similar to NLC that possess large two-photon and excited state absorption efficiencies, they are also promising candidates for ultrafast (picosecond and femtosecond) nonlinear transmission, optical limiting and pulse compression operations.…”
Section: Multiple Time Scales Nonlinearities Of Nematic Liquid Crystamentioning
confidence: 99%
“…Recently it has been developed a polarization-independent bistable light valve in a photonic crystal fiber [10] using this hysteresis effect. It has been reported that blue phase as fiber waveguiding cores are optically isotropic, polarization insensitive and relatively low-loss [11]. Khoo et al show that because of the tightly-wound director axis arrangement in blue phase, the scattering loss associated with director axis fluctuations is largely reduced and allows good transmission through long (several mm's) interaction lengths.…”
Section: Introductionmentioning
confidence: 99%